Seasonality and geographical spread of respiratory syncytial virus epidemics in 15 European countries, 2010 to 2016 - Broberg, Eeva K. (2019)
European Influenza Surveillance Network members from the contributing countries - Portugal: Raquel Guiomar, Paula Cristóvão and Pedro Pechirra (National Influenza Reference Laboratory, Infectious Diseases Department, National Institute of Health Dr Ricardo Jorge, I.P., Lisbon) and Ana Paula Rodrigues (Department of Epidemiology, National Institute of Health Dr Ricardo Jorge, I.P., Lisbon).